Electrophysiological and sick sinus syndrome effects of Remdesivir challenge in guinea-pig hearts - Li, Shuang; Yue, Liang; Xie, Yulong; Zhang, Henggui (Frontiers in Physiology, 2024)
Remdesivir (RDV) is the first drug approved by the FDA for clinical treatment of hospitalized patients infected with COVID-19 because it has been shown to have good antiviral activity against a variety of viruses, including Arenaviridae and Coronaviridae viral families. However, it has been reported that its clinical treatment leads to the symptoms of sick sinus syndrome such as sinus bradycardia, conduction block, and sinus arrest, but the electrophysiological mechanism of its specific cardiac adverse events is still unclear. We report complementary, experimental, studies of its electrophysiological effects. In wireless cardiac telemetry experiments in vivo and electrocardiographic studies in ex vivo cardiac preparations, RDV significantly caused sinus bradycardia, sinus atrial block, and prolongation of the QT interval in guinea pigs. Dose-dependent effects of RDV on the electrical activities of sinoatrial node (SA node) preparations of guinea pigs were characterised by multielectrode, optical RH237 voltage mapping. These revealed reversibly reduced sinoatrial conduction time (SACT), increased AP durations (APDs), and decreased the pacemaking rate of SA node. Patch-clamp experiments showed that RDV significantly inhibited the If current of HCN4 channels, resulting in a significant decrease in the spontaneous firing rate of SA node cells, which may underlie the development of sick sinus node syndrome. In addition, RDV significantly inhibits IKr currents in hERG channels, leading to prolongation of the QT interval and playing a role in bradycardia. Therefore, these findings provide insights into the understanding the bradycardia effect of RDV, which may be used as basic theoretical guidance for the intervention of its adverse events, and prompt safety investigations of RDV's cardiac safety in the future.